2018
DOI: 10.1080/14767058.2018.1432037
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid HIF1α and exosomal HIF1α in cervical insufficiency patients with physical examination-indicated cerclage

Abstract: This study demonstrated that amniotic fluid (AF) HIF1α and AF exosomal HIF1α were higher in physical examination-indicated cerclage (PEIC) group than control group. AF HIF1α and AF exosomal HIF1α were associated with shorter amniocentesis-to-delivery interval. More importantly, they had positive correlations with AF inflammatory cytokines such as IL1α, IL6, and TNFα. Our results may indicate that AF HIF1α and AF exosomes interact with AF inflammatory cytokines and contribute inflammatory cascade in complicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…They were therefore excluded from the first list of genes primarily linked to cervical insufficiency (n = 12; summarized in Table 2) composed from the data of the literature analysis and additional gene searches. Lastly, only one functional study was conducted to analyze HIF1A gene expression in the amniotic fluid from patients with isolated cervical insufficiency and indicated cerclage [65].…”
Section: Systematic Literature Analysismentioning
confidence: 99%
“…They were therefore excluded from the first list of genes primarily linked to cervical insufficiency (n = 12; summarized in Table 2) composed from the data of the literature analysis and additional gene searches. Lastly, only one functional study was conducted to analyze HIF1A gene expression in the amniotic fluid from patients with isolated cervical insufficiency and indicated cerclage [65].…”
Section: Systematic Literature Analysismentioning
confidence: 99%
“…In support of the etiopathological role of inflammatory cytokines in development of PTB, As Sayaril et al [24] reported higher expression of genes for IL1α, IL-1β, IL-6, and TNF-α in plasma of PTB patients than in control pregnant women. Recently, Song et al [25] detected positive correlations between amniotic fluid (AF) hypoxia-inducible factor 1α (HIF1α) and exosomal HIF1α with AF levels of IL-1α, IL-6, and TNF-α in CI patients with physical examination-indicated cerclage and suggested an interaction between AF HIF1α and exosomes and inflammatory cytokines that may induce or contribute the inflammatory cascade in complicated pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Son et al (17) assayed AF samples of women with CI for 15 cytokines and detected significantly increased levels of most of assayed cytokines compared to control women. Recently, in 2018, Song et al (18) reported significant differences in inflammatory cytokines between women with indicated cerclage and control women.…”
Section: Discussion:-mentioning
confidence: 99%
“…Also, Ito et al (21) reported that rescue CC contributes to prolonged pregnancy and promote neonate survival and was associated with a higher likelihood of reaching at least 28 weeks gestation before delivery in women with bulging fetal membranes. Recently, Song et al (18) reported that when cerclage was indicated on physical examination, AF levels of IL-1α, IL-6 and TNF-α showed significantly negative association with cerclage-to-delivery interval.…”
mentioning
confidence: 99%